Dynamic analysis of earth dam damaged by the 2011 Off the Pacific Coast of Tohoku Earthquake - Bhuddarak Charatpangoon (2018)
This study examines possible failure mechanisms and dynamic behavior of the Fujinuma dam, which failed following the 2011 Off the Pacific Coast of Tohoku Earthquake. The study comprises two parts: an investigation through field and laboratory experiments, and a numerical simulation of the dam. Field measurements and laboratory experiments were conducted to acquire necessary information. Microtremor observations of the surviving portion of the failed dam were performed to extract data from its dynamic characteristics. Triaxial and other laboratory tests provided information required for the analysis. For the seismic analysis, a coupled solid-fluid finite element method was applied and observed and simulated motions of the 2011 Tohoku Earthquake used as input. Mechanical behavior of the dam material was described using the Mohr-Coulomb failure criterion. Frequency and dynamic analyses were performed and dam behavior and possible failure phenomena presented. Furthermore, a comparison between the simulation results and existing facts is di scussed. © 2014 Elsevier Ltd.